Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.3920/bm2017.0097
|View full text |Cite
|
Sign up to set email alerts
|

New probiotic strains for inflammatory bowel disease management identified by combining in vitro and in vivo approaches

Abstract: Alterations in the gut microbiota composition play a key role in the development of chronic diseases such as inflammatory bowel disease (IBD). The potential use of probiotics therefore gained attention, although outcomes were sometimes conflicting and results largely strain-dependent. The present study aimed to identify new probiotic strains that have a high potential for the management of this type of pathologies. Strains were selected from a large collection by combining different in vitro and in vivo approa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
50
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(54 citation statements)
references
References 25 publications
3
50
0
Order By: Relevance
“…LAB exist in a wide range of habitats, including gastrointestinal (GI) tracts, oral cavities, vaginal tracts of humans and animals, fermented foods, silages, and composts (7). They possess various health benefits to the host, such as enhancement of immune function (8), improved digestion (9), management of inflammatory bowel diseases (10), alleviation of constipation (11), and strengthening the mucosal barrier (12). Some LAB isolates even hold anticancer or antidiabetic effects (13,14).…”
Section: Introductionmentioning
confidence: 99%
“…LAB exist in a wide range of habitats, including gastrointestinal (GI) tracts, oral cavities, vaginal tracts of humans and animals, fermented foods, silages, and composts (7). They possess various health benefits to the host, such as enhancement of immune function (8), improved digestion (9), management of inflammatory bowel diseases (10), alleviation of constipation (11), and strengthening the mucosal barrier (12). Some LAB isolates even hold anticancer or antidiabetic effects (13,14).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, studies characterizing gut microbiota composition and its modi cation during UC are relevant, since: a) UC provides a higher risk for colorectal cancer, whereas gut dysbiosis is thought to facilitate colorectal cancer development; b) the study of gut microbial communities during clinical phases of UC contributes to a better understanding of potential interactions with host immune response; c) characterization of speci c genus of gut microbial communities may own potential clinical application derived from their association with active or remission phases of UC; and d) speci c microbial manipulation, concomitant to antibiotic use, is currently used as a therapeutic approach for UC [49,60,61].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, this feature was maintained in both CD and UC patients, despite their gut microbiome dysbiosis. Bi dobacterium has been shown to have bene cial effects for human health, such as improving mucosal barrier function and reducing in ammation by producing short-chain fatty acids and vitamins, and is used in probiotics as one treatment option for IBD [34][35][36][37]. A previous Western study analyzing the treatment-naïve CD microbiome showed that Bi dobacterium abundance decreased in CD patients [7].…”
Section: Discussionmentioning
confidence: 99%
“…The high abundance of Bi dobacterium in the gut microbiome of Japanese individuals was considered as a potential factor explaining the low IBD prevalence in Japanese populations; however, in our study, this unique feature was detected not only in healthy individuals but also in IBD patients. Members of the genus Bi dobacterium can have species-dependent effects [34,36,37], and thus further species-level research is needed to understand the role of Bi dobacterium in the pathogenesis of IBD.…”
Section: Discussionmentioning
confidence: 99%